Pilot study: Impact of plyometric training on goalkeepers` ball-blocking performance in football penalty situations - Dawood, Q. Q. (International Journal of Kinesiology & Sports Science, 2025)
Background: Developing Goalkeeper`s performance is imperative to defence the goal. As the Football match`s nature needs implementning the skill with strength, and speed. so, the Goalkeeper demands special physical abilities that enabling him the ball blocking skill masterly.